Cardiovascular comorbidities, inflammation, and cerebral small vessel disease. Issue 13 (9th September 2021) - Evans, Lowri E; Taylor, Jade L; Smith, Craig J; Pritchard, Harry A T; Greenstein, Adam S; Allan, Stuart M
Abstract: Cerebral small vessel disease (cSVD) is the most common cause of vascular cognitive impairment and affects all levels of the brain's vasculature. Features include diverse structural and functional changes affecting small arteries and capillaries that lead to a decline in cerebral perfusion. Due to an ageing population, incidence of cSVD is continually rising. Despite its prevalence and its ability to cause multiple debilitating illnesses, such as stroke and dementia, there are currently no therapeutic strategies for the treatment of cSVD. In the healthy brain, interactions between neuronal, vascular, and inflammatory cells are required for normal functioning. When these interactions are disturbed, chronic pathological inflammation can ensue. The interplay between cSVD and inflammation has attracted much recent interest, and this review discusses chronic cardiovascular diseases, particularly hypertension, and explores how the associated inflammation may impact on the structure and function of the small arteries of the brain in cSVD. Molecular approaches in animal studies are linked to clinical outcomes in patients, and novel hypotheses regarding inflammation and cSVD are proposed that will hopefully stimulate further discussion and study in this important area. Graphical Abstract: